PHOTODEGRADATION OF Cr (VI) IN VARIOUS CONCENTRATION OF ZSM-5 IMPREGNATED TIO2 - Alfiani, Yulia; Mukaromah, Ana Hidayati; Sulistyaningtyas, Ayu Rahmawati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Nowadays,water could be contaminated by heavy metals such as chromium (Cr). Chromium toxicity depends on its state of valence. Cr (VI) as highly mobile is toxic, while Cr (III) as a less mobile is less toxic. Potentially, Cr (VI) content   can be reduced by ZSM-5 impregnated TiO2. TiO2  as a catalyst can activated and modified zeolite with active metal materials. The impregnation between ZSM-5 and TiO2 should be reduce Cr (VI) content in water. The objective of this study was to assess concentration of ZSM-5 impregnated TiO2 which  most  effectively  for  decreasing  Cr  (VI)  content.  Decreasing  Cr  (VI) content in various concentration of ZSM-5/TiO2  was measured using UV-Vis spectrophotometer. The results showed that variation of zeolite concentration had an effect on decreasing Cr (VI) content in water. Photodegradation of Cr (VI) in various concentrations (0.25%;0.50%; 0.75%; 1.00%; 1.25% w/v) respectively are 16.99%; 18.84%; 24.83%; 30.82%; 36.14%. Concentration 1.25% w/v of ZSM-5 impregnated TiO2   as the highest to decrease Cr (IV) content. On the other hand, Using TiO2  or ZSM-5 only was showing lower percentage of Cr (VI) reduction which compared ZSM-5/TiO2. In conclusion, More higher concentration ZSM-5/TiO2  caused   faster photodegradation and higher percentage decrease of Cr (VI) content in water. Keywords: Concentration, Cr (VI),  Photodegradation, TiO2, ZSM-5